2017
DOI: 10.1002/jccs.201700256
|View full text |Cite
|
Sign up to set email alerts
|

Novel I–V Disposable Urea Biosensor Based on a Dip‐coated Hierarchical Magnetic Nanocomposite (Fe3O4@SiO2@NH2) on SnO2:F Layer

Abstract: Silicon oxide was initially loaded on a Fe3O4 magnetic nanoparticle substrate (Fe3O4@SiO2) and then functionalized with ─NH2 group (Fe3O4@SiO2@NH2) to construct a novel hierarchical magnetic nanocomposite. A sensitive urea biosensor medium involving a dip‐coated hierarchical magnetic nanocomposite on F‐doped SnO2 conducting glass was designed (Fe3O4@SiO2@NH2/SnO2:F) to achieve an excellent platform for urease (Urs) enzyme immobilization via covalent linking to the exposed NH2 groups through glutaraldehyde (Urs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Among the tested substances, NaCl exhibited the biggest interfering signal; however, this change was relatively small in comparison to urea response. It has been observed that especially the interference effect of glucose and ascorbic acid is lower than other urea biosensors [55, 57, 60, 61]. The results showed that the prepared biosensor is suitable for the selective detection of urea in real samples such as municipal wastewater and blood serum, containing glucose and ascorbic acid.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Among the tested substances, NaCl exhibited the biggest interfering signal; however, this change was relatively small in comparison to urea response. It has been observed that especially the interference effect of glucose and ascorbic acid is lower than other urea biosensors [55, 57, 60, 61]. The results showed that the prepared biosensor is suitable for the selective detection of urea in real samples such as municipal wastewater and blood serum, containing glucose and ascorbic acid.…”
Section: Resultsmentioning
confidence: 91%
“…Among the tested substances, NaCl exhibited the biggest interfering signal; however, this change was relatively small in comparison to urea response. It has been observed that especially the interference effect of glucose and ascorbic acid is lower than other urea biosensors [55,57,60,61].…”
Section: Effect Of the Possible Interfering Substances On Biosensor P...mentioning
confidence: 99%
“…Proved amazing and unique properties of these structure led to a widespread use of them in various categories of science, including medicine, industry and technology. Due to their inherent features, SWCNTs are able to not only Review Article deliver the bioactive molecules across cell membranes, but also into the cell nuclei because of their very high surface areas [5][6][7][8]. Certain theoretical studies on the behaviors of 1, 3-dipolar cycloadditions on the (n,n) SWCNTs have been performed and the results of this investigation have been reported by the authors [9].…”
Section: Introductionmentioning
confidence: 90%
“…The outer silica shell stabilizes Fe 3 O 4 nanoparticles in solution as well as provides reactive sites on its surface for functionalization [21,22]. Amine groups are one of the active functional groups that can lead to the functionalization of the aforementioned SiO 2 surface or silicate shell through the reaction of aminoalkyl triethoxysilane with the silica surface [23,24]. In the following, other additives (like S-contents compounds) and compression reactions can be performed on this amino nucleophile group to reach the desired level [25].…”
Section: Introductionmentioning
confidence: 99%